Synthesis and Reactivity of A Novel Polar Tin Hydride - BRAIA, N.; SAIHI, Y.; AZZOUZI, A.E.; FERKOUS, F. (Asian Journal of Chemistry, 2010)
The organostannic compounds are well known for use in organic synthesis. However, their use presents a major disadvantage because of their high toxicity and the difficulty in the separation of organostannic residues in the synthesis process. In order to overcome this problem, a polar tin hydride is synthesized, which showed a remarkable reactivity with the great advantage of being able to easily recuperate organostannic residues which will be then recycled.